Work and Well-Being of Informal Caregivers in Europe - Dörte Heger (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
Informal caregivers provide valuable services to elderly persons with long-term care needs, but the consequences of caregiving on caregivers are not yet fully understood. This paper illustrates the interrelation between caregiving and caregivers' labour force participation, cognitive ability, and health in a simple theoretical model, and estimates the effects of caregiving using panel data from 13 European countries, which allows to analyze the effect of institutions on caregivers' outcomes. The results show that caregiving severely and signicantly reduces caregivers' probability of being employed, but only in countries with few formal care alternatives. Furthermore, caregivers in all countries suffer from worse mental health when caregiving is prompted by poor parental health. The results for the effects of caregiving on physical health and cognitive ability are mixed. – – Informelle Pflegerinnen und Pfleger leisten einen wertvollen Beitrag zu der Pflege älterer Menschen. Welche Folgen die Erbringung von Pflege auf die pflegende Person hat, ist jedoch noch nicht vollständig bekannt. Diese Studie verdeutlicht den Zusammenhang zwischen Pflegeerbringung, Arbeit, kognitiven Fähigkeiten und Gesundheit in einem theoretischen Modell und schätzt die Auswirkung von Pflegeerbringung anhand von Längsschnittdaten aus 13 europäischen Ländern. Dabei wird insbesondere der Einfluss institutioneller Faktoren auf die Auswirkungen von Pflegeerbringung analysiert. Die Ergebnisse zeigen, dass Pflegeerbringung die Erwerbstätigkeit in Ländern mit einem geringeren professionellen Pflegeangebot stark reduziert. Dagegen leiden in allen Ländern pflegende Personen häufiger an depressiven Symptomen. Die Ergebnisse für kognitive Fähigkeiten und Gesundheit sind gemischt.
Keywords: I12; J14; J18; J22; 330; informal care; labour supply; cognitive ability; physical and mental health